A study on the origin of the oracle bone inscription "qin" (禽). (June 2019) - Park, Seok-hong
The oracle bone graphic qin "禽" is known as a character related to the hunting culture of ancient China. Qin is generally considered to be a hunting tool for birds, but there is still room for discussion as to what kind of hunting implements this graph depicted. This paper proposes a different hypothesis concerning the origin of the shape of qin based on various studies on Chinese ancient characters and ancient hunting cultures to help draw logical conclusions about the origin of the shape of qin .